Pendampingan Terapi Aktivitas Kelompok terhadap Kepatuhan Medikasi pada Penderita Diabetes Melitus di Puskesmas Siko, Kota Ternate - Abubakar, Amira Bin Seh; Idrus, Fitriyanti N.; Umanailo, Damir (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Several things, including patient compliance influence diabetes management in medicine. Group Activity Therapy can be used as a therapeutic modality for education, counseling, and motivation for diabetes sufferers in taking medication. This service activity aims to provide TAK assistance to increase knowledge and medication compliance for Diabetes Mellitus sufferers. The service method is carried out with the assistance of Group Activity Therapy, which consists of an introduction to Diabetes Mellitus, medication compliance, and evaluation of medication compliance for Diabetes Mellitus sufferers. The results and outcomes obtained were an increase in knowledge of medication adherence in Diabetes Mellitus sufferers at the Siko Community Health Center, namely from 25 participants whose initial pretest results for medication knowledge were 48% good and 52% adequate, at the posttest the good knowledge increased to 92% and 8% adequate. Apart from that, there was an increase in medication compliance, from the pretest result of medication compliance being 36% compliance and 64% non-compliance after the posttest to 96% compliance and 4% non-compliance. Diabetes Mellitus sufferers are expected to be able to maintain their compliance with active medication by carrying out routine control at the Community Health Center.